Potensi Agregat Lokal Desa Ouw, Kecamatan Saparua Timur, Kabupaten Maluku Tengah Sebagai Pembuat Beton - Greace Vilda Saptenno; Pieter Lourens Frans; Maslan Abdin (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
Concrete is a major construction material whose quality and strength are highly influenced by aggregate characteristics. This study utilized sand and coral from Motoni Beach, Ouw Village, East Saparua District, Central Maluku, to evaluate their feasibility as constituents of normal concrete. The objective was to design a concrete mixture with a target strength of 20 MPa and to analyze the resulting compressive strength. The research method was experimental in a laboratory, including aggregate characterization tests (moisture content, silt content, specific gravity, absorption, and Los Angeles abrasion), mix design calculation, preparation of cylindrical specimens (Ø15×30 cm), curing, and compressive strength tests at the ages of 7, 14, and 21 days. The results showed that Motoni sand met SNI requirements, while coral aggregate exhibited high absorption (7.30%), making it unsuitable as coarse aggregate for structural concrete. The maximum compressive strength was obtained at 14 days, reaching 21.69 MPa, but decreased to 17.17 MPa at 21 days, equivalent to 18.07 MPa at 28 days (conversion based on PBI 1971). This value did not meet the planned strength of 20 MPa. In conclusion, Motoni Beach sand is suitable as fine aggregate, whereas coral aggregate is only applicable for non-structural purposes.Keywords: Concrete, Beach Sand, Coral, Compressive Strength